Syntactic architecture and its consequences II Between syntax and morphology - Biberauer, Theresa; Vikner, Sten; Bárány, András; Douglas, Jamie (Language Science Press, 2020)
This volume collects novel contributions to comparative generative linguistics that "rethink" existing approaches to an extensive range of phenomena, domains, and architectural questions in linguistic theory. At the heart of the contributions is the tension between descriptive and explanatory adequacy which has long animated generative linguistics and which continues to grow thanks to the increasing amount and diversity of data available to us.The chapters address research questions in comparative morphosyntax, including the modelling of syntactic categories, relative clauses, and demonstrative systems. Many of these contributions show the influence of research by Ian Roberts and collaborators and give the reader a sense of the lively nature of current discussion of topics in morphosyntax and morphosyntactic variation.This book is complemented by volume I available at https://langsci-press.org/catalog/book/275 and volume III available at https://langsci-press.org/catalog/book/277.